Determinants of Lecturer Performance in Vocational Higher Education in Banten: The Role Of Organizational Learning, Capability, and Stakeholder Commitment - Feby Arma Putra; Sudiharto Sudiharto (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to determine the effect of learning organization, capability on lecturer performance with stakeholders as intervening variables. This study used a descriptive quantitative method with a population of permanent lecturers at a private Polytechnic in Banten. Samples were taken by using proportional random sampling technique, 158 lecturers. Technical data analysis using Partial Least Square method and Structural Equotion Model (PLS-SEM) with SmartPLS 3.0 application. The results indicate that learning organization and capability have positive and significant effects on stakeholder commitment and lecturer performance. Stakeholder commitment also positively and significantly influences lecturer performance and mediates the relationships between learning organization, capability, and lecturer performance.